Hubungan Safety Talk Dengan Kecelakaan Kerja Pada PT. Pelindo Terminal Petikemas New Makassar Terminal 2 - Radita Anggraeni Putri; Suharni A. Fachrin; Arman (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Safety talk is an activity carried out before work by providing material to remind workers that occupational health and safety (K3) is important in a job. This study aims to determine the relationship between safety talk and work accidents at PT. Pelindo Terminal Petikemas New Makassar Termina 2. Pelindo Terminal Petikemas New Makassar Termina 2. This type of research uses a quantitative method with a cross-sectional study design with a population of 77 workers and a sample of 77 workers using total sampling. Data analysis was done univariately and bivariately using the chi-square test to determine the related variables. The results of this study show that the p-value of knowledge with work accidents is 0.609, the p-value of education with work accidents is 0.498, and the p-value of compliance with work accidents is 0.000. A p-value less than 0.05 is considered statistically significant, indicating a strong relationship between the variables. Therefore, it can be concluded that the influential variable is compliance with work accidents. This study concludes that compliance is a variable related to work accidents. The suggestion from this study is that it is hoped that the company will provide training to workers regarding the importance of occupational health and safety (K3).